Fairy tales of hans christian andersen ebook - Andersen, Hans Christian (Duke Classics, 2012)
Danish author and poet Hans Christian Andersen is regarded as one of the most important figures in the genre of children's literature. With tales such as The Ugly Duckling, The Little Mermaid, The Steadfast Tin Soldier, The Snow Queen, Thumbelina , and The Little Match Girl , Andersen has captivated generations of readers around the globe. This collection presents an array of Andersen's most beloved fairy tales.